Extentional Fault Pada Daerah Compressive Tectonic Zone Sebagai Batas Cekungan Di Jawa Tengah Selatan - Asmoro Widagdo; Aang Panji Permana (Universitas Negeri Gorontalo, 2021)
The extensional structure as a normal fault could be found in many places at the southern part of Java compressive tectonic regime. The research area is in the eastern part of the South Serayu Mountains. This normal fault structure is the boundary of the South Serayu Mountains at the eastern part with Kulon Progo Tertiary volcanic Mountains. In the field, these normal fault lineament zones create the Bogowonto river as a boundary of two different geological styles. The influence of this structure on the geological dynamic of the South Serayu Mountains and the Kulon Progo Mountains is important to be explained. The study was conducted by measuring and analyzing fault data and lithology that developed in the area around the two basins boundary. The distribution of the Kulon Progo volcanic rocks indicates the presence of the extensional fault structure. The volcanic facies distribution of the volcano is cut and becomes narrow in the west, while the northward is very wide. Normal fault striations analysis on the fault plane along the fault line shows the least stress trending west-northwest that has worked to create North-South normal faults. The fault-controlled by stress with the vertical main compression area. They have worked to create North Northeast-South Southwest (NNE-SSW) normal faults with westward dipping.